The impact of ethnicity on chronic hepatitis B infection course and outcome: big data analysis from Israel. Issue 3 (3rd April 2023) - Abu Baker, Fadi; Ben Ari, Ziv; Green, Ilan; Israel, Areil; Kopelman, Yael; Abu Mouch, Saif; Davidov, Yana; Khoury, Tawfik; Mari, Amir
ABSTRACT: Objectives: The effect of ethnicity on chronic hepatitis B virus (CHB) infection's course and outcome has attracted little research. We aimed to compare different aspects of ethnic disparities in CHB patients, including prevalence, phenotypes, management, and outcome between two major ethnic groups in Israel. Design: We conducted a large retrospective cohort study utilizing the Leumit-Health-Service database. Electronic reports of almost 700, 000 members from different ethnicities and districts throughout Israel from 2000 to 2019 were reviewed. Patients' ethnicity was categorized based on the classification of the Israeli Central Bureau of Statistics into two main groups, Arabs and Jews. CHB diagnosis was based on ICD-9-CM codes and supportive serology results. Prevalence, clinical backgrounds, disease course, and patients' outcomes were compared between both groups. Results: The prevalence of CHB in the Arab minority group was almost twice and a half-higher when compared to their Jewish counterparts (4.3% vs. 1.8%), but they had a lower rate of referral for HBsAg testing (7% vs. 7.9%). The Arab CHB patients were significantly younger at the time of diagnosis (37.6± 13.5 vs. 45.3± 15; P  < 0.001). Male predominance was noted in both groups. The Arab patients had a higher rate of active hepatitis (HBeAg-positive and/or negative hepatitis) phase (36.4% vs. 29.8%; P  = 0.01), as well as a significantly higher rate of HBeAg seroconversion (45.2% vs. 35.4%; P  = 0.033). Nucleos/tide analogue treatment figures were similar, with most patients in both groups receiving a high barrier to resistance treatment. Patients' outcome was similar in both groups as the rate of hepatocellular carcinoma, cirrhosis, and advanced fibrosis (after stratification analysis) were comparable between both groups. Conclusion: Marked by a prominently higher prevalence of HBV infection, patients in the Arab ethnic group had a lower rate of referral for HBsAg testing but received comparable management and had a similar outcome compared to their Jewish counterparts.